Heritage, endangerment and participation: alternative futures in the Lake District. Issue 1 (2nd January 2020) - May, Sarah
ABSTRACT: Cultural heritage policy in the UK puts a high value on participation, and heritage agencies often encourage that participation through appealing to the endangered status of the landscapes, sites and monuments in their care. Participation takes many forms, and can involve influencing policy, contributing to cultural outputs and enjoying cultural activities. This paper critically examines the literature and discourse underpinning the endangerment/participation axis and presents a case study of heritage participation in the English Lake District. In order to ground critique in empirical investigation, the case study focusses on the practice of a particular fell shepherd, whose participation in heritage is not motivated by endangerment. The paper then explores the implications of this research for wider thinking about heritage and public life, arguing for the importance of moving beyond endangerment narratives for the creation of resilient heritage futures.